Computational statistics : an introduction to R - Sawitzki, Günther. (Boca Raton : CRC Press, 2009)
The book illustrated how to use the freely available R software package for data analysis, statistical programming, and graphics. Integrating R code and examples throughout, the text only requires basic knowledge of statistics and computing.
A Chapman & Hall book.
Includes bibliographical references (p. 233-235) and indexes.
rpm 24/05/13
Loans
Keywords: R (Computer program language); Mathematical statistics